Uma sala de cinema para a Geração Z : um projeto baseado no design de experiência - Lemos, Felipe Macedo (2024)
The general objective of this work was to develop a new disruptive movie theater format, aimed at Generation Z, with a focus on creating an immersive cinematic experience. The study addressed the historical and technological evolution of cinema; delved deeper into the study of reference brands focused on the concept of experience; and sought to identify young adults' habits and preferences about cinema consumption in Brazil. The research methodology included qualitative and quantitative methods, such as literature review, questionnaire, and direct observation. The data collected revealed that young people from Generation Z have a strong preference for immersive and technologically advanced experiences. A comparative analysis of different cinema formats helped outline the new project, ensuring that the experience was designed in a user-centric way. The project was developed with tools specific to Experience Design, such as creating personas, empathy maps and user journeys, and focused on new technologies that could be implemented to meet the expectations of its specific audience. The conclusion of this dissertation demonstrates that the established objectives were achieved, proposing a new model for the future of cinemas, which seeks to guarantee their relevance and sustainability in a constantly evolving market.